The Interests Continue to University and The Affecting Factors on Third Grade Senior High School in Kepenuhan Subdistrict Rokan Hulu Regency - Erma Yunita; Gimin Gimin; Sumarno Sumarno (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2018)
This study aims to analyze the influence of continuing high academic interest and the factors that influence it. The population of this study is the students of Class XII Secondary Education in KepenuhanSubsubdistrict as much 137 students. The research was conducted with a sample of 102 students the measurementwith Proportional Random Sampling technique, using questionnaires. The data analysis used in this research is quantitative descriptive and path analysis. The results of the research showed that generally the interest of continue to university students of grade XII Secondary Education in Kepenuhansubsubdistricthas highinterest (43.14%), even 34.31% in very high category. The interest is influenced by ambition factor, family environment and school environment with direct donations of 16.72%, 4.66%, 38.44%. While the indirect contribution of family environment and school environment to the interest through aspirations of each 3.09%, 32.14%.